Multimodalne značilnosti izvirnih slovenskih slikopisov - Haramija, Dragica (Revija za elementarno izobraževanje, 2023)
The article presents the characteristics of original Slovene rebus stories that have been published in book form in the last five years. Systematically also older (original and translated) rebus stories were looked at, so we are able to suggest that the findings can be applied more generally to this particular form of reading material that has a distinctly didactic function in the learning to read or developing reading literacy phase. Our research focuses on the types of literary genre and themes that appear in rebus stories, the place of illustrations in these stories, and into the characteristics of quality rebus stories. Through the analysis of 24 rebus stories, we identified the genre and themes of these stories as well as their design aspect (the position of illustrations). Through a multimodal analysis of selected work we also identified the basic characteristics of quality rebus stories.
Keywords: components of reading literacy; gradniki bralne pismenosti; multimodality; multimodalnost; muzej; picture book; rebus story; slikanica; slikopis; structuralism; strukturalizem